Evaluating bioenergy potential of eastern redcedar (Juniperus virginiana L.) stands using a small unmanned aerial system (sUAS) - Burchfield, David R.; Price, Kevin; Bryant, Johnny; van der Merwe, Deon; Wang, Huan; Armbrust, Ryan; An, Nan (Kansas State University, 2013)
Due primarily to changes in land management practices, Eastern redcedar (Juniperus virginiana L.), a native Kansas conifer, is rapidly invading onto valuable rangelands. The suppression of fire and increase of intensive grazing combined with the rapid growth rate, high reproductive output, and dispersal ability of the species have allowed it to dramatically expand beyond its original range. A 2002 study of redcedar expansion in Oklahoma reported an economic loss of $447 million by 2013 and an invasion rate of 762 acres per day. There is a growing interest in harvesting this species for use as a biofuel. For economic planning purposes, density and biomass quantities for the trees are needed. High resolution color-infrared imagery was collected over redcedar stands in Riley County, Kansas using a Canon S100 camera modified to collect images in near-infrared, green, and blue wavelengths. The camera was flown aboard a DJI S800 hexcopter over redcedar stands to collect the imagery. The imagery was processed to produce an orthophoto and 3D model from which individual redcedar tree biophysical properties were assessed. Using allometric equations, trees were evaluated for total aboveground biomass and British Thermal Unit (BTU) potential. The methods shows considerable promise for sites where tree canopy is not coalescing and individual tree canopy size can be determined.
Keywords: Eastern redcedar; Juniperus virginiana L.; Unmanned air vehicles; Infrared imagery